Antecedents and consequences of experienced workplace incivility among millennial employees - Reny Yuniasanti (2022)
Research into workplace incivility has received little attention in Indonesia, especially in identifying the cause and implication of experienced workplace incivility among millennial employees. In the future, millennial employees will take up the highest proportion of employees in Indonesia. Therefore, this study aimed to identify the antecedents and the consequences of experienced workplace incivility using Affective Events Theory (AET), Conservation of Resources Theory (COR), Theory of Social Power, and Social Exchange Theory. Data were collected via online questionnaires from employees of two private organizations (n = 230) through a purposive sampling technique. The questionnaires consist of demographic data questions and five measurements, namely Workplace Incivility Scale, Emotional Exhaustion, Psychological Well-being, Culture Values, and Turnover Intention. Analysis of the research using PLS-SEM showed the presence of experienced workplace incivility among millennial employees due to types of employees ( = -0.161, p< 0.05), age ( = 0.153, p< 0.05) and collectivism dimension of cultural values ( = -0.415, p< 0.05). Analysis showed that emotional exhaustion mediates experienced workplace incivility, psychological well-being ( = -0.365, p<0.05), and turnover intention ( = 0.228, p <0.05). This study discovered that gender ( = 0.319, p>0.05), hierarchical status ( = 0.135, p>0.05), and the dimension of cultural values of individualism ( = 0.006, p> 0.05) are not significant factors in the experience of uncivil behavior from supervisors or co-workers. This research showed that psychological well-being is not significantly correlated with turnover intention ( = 0.125, p>0.05) among the millennial generation. In practice, this study can shape workplace policies by designing an intervention to create a civil environment, manage emotional exhaustion, enhance psychological well-being, and reduce turnover intention. This research will inspire future research in the 4.0 Industrial Revolution Era to explore the possibility of online incivility toward millennial employees rather than in-person incivility.